Evolution of Micron-Scale Pore Structure and Connectivity of Lignite during Pyrolysis - Qiaorong Meng; Yangsheng Zhao; Zhiqin Kang; Yong Wang; Li Gao; Yongfeng Zhang (Advances in Materials Science and Engineering)
Based on the high-precision microcomputed tomography (micro-CT) technology, the evolution of the μm-scale pore structure and connectivity of lignite during pyrolysis from room temperature to 600°C was studied. The results show that the pore connectivity of lignite increases with the increase of temperature, and the change of pore structure can be divided into four stages: the first stage is from room temperature to 100°C, characterized by generation and connection of small-diameter pores. The second stage is 100–200°C, characterized by rapid expansion and interconnection of pores due to the thermal cracking. The third stage is from 200°C to 450°C, characterized by the slow evolution of pore structure for pyrolysis. The fourth stage is from 450°C to 600°C, characterized by pore interconnection for pyrolysis. 200°C is the temperature at which the μm-scale pore structure of lignite changes dramatically. During the whole pyrolysis process from room temperature to 600°C, the pore quantity of lignite is mainly from the pores of a diameter of 0.65–3 μm. At 200°C and above, the pore volume of lignite is mainly from the pores with a diameter larger than 100 μm, but they are few. These research results have important theoretical reference values for the upgrading and pyrolysis of lignite.